2006
DOI: 10.1097/01.jcp.0000246214.49271.f1
|View full text |Cite
|
Sign up to set email alerts
|

n-3 Polyunsaturated Fatty Acids Decrease Anxiety Feelings in a Population of Substance Abusers

Abstract: There is mounting evidence that low levels of n-3 polyunsaturated fatty acids (PUFAs) play a role in the pathophysiology of a number of psychiatric disorders. Preclinical studies have shown that n-3 PUFAs decrease anxietylike behaviors, but there is a paucity of information about their effects on anxiety in humans. In light of our observation that substance abusers have poor dietary habits and the strong association between anxiety disorders and substance use disorders, the possibility that the administration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 15 publications
0
39
1
Order By: Relevance
“…A group of patients was studied and found to have a suboptimal dietary intake of long chain (LC) n-3 PUFAs. Significant decreases in anger and anxiety scores following a 3-month treatment with a daily dose of 2.25 g of EPA, 500 mg of DHA and 250 mg of other n-3 PUFAs were observed in these patients (Buydens-Branchey and Branchey, 2006;Buydens-Branchey and Branchey, in press). Plasma samples had been collected in these patients prior to the start and at the end of the therapeutic trial but fatty acids (FAs) levels had not been determined in these samples and no association could thus be established between changes in anger and anxiety scores and biochemical changes.…”
Section: Introductionmentioning
confidence: 81%
“…A group of patients was studied and found to have a suboptimal dietary intake of long chain (LC) n-3 PUFAs. Significant decreases in anger and anxiety scores following a 3-month treatment with a daily dose of 2.25 g of EPA, 500 mg of DHA and 250 mg of other n-3 PUFAs were observed in these patients (Buydens-Branchey and Branchey, 2006;Buydens-Branchey and Branchey, in press). Plasma samples had been collected in these patients prior to the start and at the end of the therapeutic trial but fatty acids (FAs) levels had not been determined in these samples and no association could thus be established between changes in anger and anxiety scores and biochemical changes.…”
Section: Introductionmentioning
confidence: 81%
“…The study found increased seafood consumption during pregnancy was associated with decreased behavioural problems; however, (159) C substance abusers 24 (13/11) 2·25 g EPA þ 0·5 g DHA þ0·25 g other n-3PUFA (161,162) ; HAQ-C, Hostility-Aggression Questionnaire for Children (163,164) ; w-s, within-subjects; POMS, Profile of Mood States (anger question, tension question) (136) ; STAXI, State-Trait Anger Expression Inventory (165) ; C, clinical; ADHD, attention deficit hyperactivity disorder; ABC, Aberrant Behaviour Checklist (166) ; MOAS, Modified Overt Aggression Scale (137) ; E-EPA, ethyl ester EPA; n-6PUFA, n-6 long-chain PUFA.…”
Section: Epidemiological Evidencementioning
confidence: 87%
“…And finally, decreased levels of most n–3 polyunsaturated fatty acids have been found in the red blood cell membranes of patients with social anxiety disorder [19] as well as in those with mood disorders [12,20]. Investigators such as Horrobin, Buydens-Branchey, and their colleagues [13,14,20,21,22] have demonstrated that supplementation of these essential fatty acids may help to improve outcomes across several domains of psychopathology, including aggression.…”
Section: Introductionmentioning
confidence: 99%